THE ROLE OF AERIAL PHOTOGRAPHY IN THE CREATION OF TOPOGRAPHIC MAPS - Tukhtamishev Shukhrat Shermanovich; Khudaykulov Shoxruz Shukhrat o’g’li; Omonov Ismail Kholboevich (International Engineering Journal For Research & Development, 2020)
The purpose of this article is to help organizations that produce the essence and features of the PHOTOMOD program to create an aerospace industry that will make it easier, more efficient, and more efficient.